2021
DOI: 10.7759/cureus.16675
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Glioblastoma Patient Symptoms to Diagnose and Predict Survival

Abstract: Glioblastoma is a devastating malignancy with a dismal survival rate and median survival time of 14 months. Currently, the biomarkers for glioblastoma are mostly molecular and include EGFRvIII, ATRX, PTEN, IDH1, MGMT, and others. These prognostic tumor biomarkers are obtained through a surgical biopsy and thus are not easily attainable. Clinicians would benefit from a robust, non-invasive, and readily available indicator for early diagnosis and accurate prognostication for glioblastoma patients. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The pathological classification of primary brain tumours follows the WHO grading system, which consists of grades of I–IV, unlike other cancers. A higher grade of PMBT tends to be associated with more severe symptoms and a higher mortality rate (Mrowczynski et al, 2021). While additional evidence is needed to demonstrate that the pathophysiological characteristics of PMBT affect cognitive‐psychological distress such as UI, this review suggests that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological classification of primary brain tumours follows the WHO grading system, which consists of grades of I–IV, unlike other cancers. A higher grade of PMBT tends to be associated with more severe symptoms and a higher mortality rate (Mrowczynski et al, 2021). While additional evidence is needed to demonstrate that the pathophysiological characteristics of PMBT affect cognitive‐psychological distress such as UI, this review suggests that this may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…This review confirmed that representative measurement tools were used in previous studies; however, developing tools to measure the cognitive and psychological variables of PMBT individuals, along with UI, still poses a challenge. While people with cancer generally experience A higher grade of PMBT tends to be associated with more severe symptoms and a higher mortality rate (Mrowczynski et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The current standard of care for GBM involves surgical resection which is later followed by a combination of radiation therapy and concurrent temozolomide chemotherapy. This approach has demonstrated an improvement in patient survival by extending the median survival from 12.1 months with RT alone to 14.6 months [5][6][7]. Despite these advancements, recurrence is inevitable within 6-9 months post-surgery, and patients typically survive fewer than 15 months post-recurrence with this aggressive regimen [8].…”
Section: Introductionmentioning
confidence: 99%
“…The subsequently increasing intracranial pressure results in loss of consciousness and finally, if not treated adequately in death. 17 This tumour originates mainly as a primary tumour with malignant features (90% of cases diagnosed with GBMs) and is classified as grade WHO IV, while in 10% of the cases it develops as secondary tumour arising from a previously diagnosed low grade astrocytoma or oligodendroglioma WHO II or WHO III. In this review, we followed the former WHO classification of gliomas, indicated using Roman numbers I–IV, to align with the studies considered for the review, where patients were stratified according to this historic classification, and not according to the molecular parameters in the revised WHO classification (1–4) from 2021.…”
Section: Introductionmentioning
confidence: 99%